Sains et saufs. - Gunti, Claus; Le Breton, David (Lausanne ; Gollion : Musée de design et d'arts appliqués contemporains (mudac) : Infolio éditions, 2016)
Mettraux, Sébastien ; Banchini, Leopold ; Zamarbide, Daniel ; Marika, Bujar ; Norman, Nils ; Gupta, Shilpa ; Meindertsma, Christien ; Kabiljo, Dejana ; Begley, Josh ; Pater, Ruben ; Bridle, James ; Menner, Simon ; Ruff, Thomas ; Paglen, Trevor ; Ruggiero, Daniel ; Dunne, Anthony ; Raby, Fiona ; Jessee, Forrest ; Cafaggi, Vittorio Dainese ; Haupt, Anna ; Alstin, Terese ; Auger, James ; Loizeau, Jimmy ; Murray, Alan ; Ramamoorthy, Subramanian ; Deschamps, Timothé ; Gnazzo, Paolo ; Lehanneur, Mathieu ; SEN.SE ; Houy, Xavier ; Soares, Susana ; Veldhuijzen van Zanten, Julia ; Studio GGSV ; Zwiggelaar, Reyer ; Al Rajoub, Bashar ; Humans since 1982 ; Hecht, Sam ; Colin, Kim ; Industrial Facility ; SUPERLIFE design studio ; Gaaloul, Edrris ; Verdon, Cyrille ; Brutter, Arthur ; Bruno, Ido ; ECAL ; D'Esposito, Martino ; Bag ; Kawai, Takayuki ; Nezu, Kota ; znug design ; Meldaikyte, Gabriele ; Swann, David ; Edward, David ; Meda, Alberto ; Gomez Paz, Francisco ; The Empowerment Plan ; Orta, Lucy ; Orta, Jorge ; Henner, Mishka ; Selvaggio, Leonardo ; Gao, Ying ; Baechtold, Claude
Schenking Flanders DC
Safe and sound. Surveillance and protection in the 21st century, Museum of Design and Contemporary Applied Arts (mudac), Lausanne, 23 March to 21 August 2016
boek